Tear film stability over a myopia control contact lens compared to a monofocal design - Garcia-Marques, Jose Vicente (2022)
Background: To compare the short-term effect of two contact lenses on pre-lens tear film stability and comfort: dual-focus contact lens (MiSight) and a monofocal contact lens (Proclear 1-day).Methods: This randomised, double-masked, crossover study was performed in twenty-eight healthy, myopic volunteers aged between 18 and 32 years (23.5 +/- 4.1 years). Only one randomly chosen eye was assessed. Distance vision and refraction were evaluated at baseline. Each contact lens type (monofocal and dual-focus) was randomly fitted, always in both eyes. A visual analogue scale between 0 and 10 was used to assess general comfort, physical comfort, and visual comfort. Tear Film Surface Quality (TFSQ) index, TFSQ_area and auto Tear Break-Up Time were obtained using Medmont E-300 at baseline (naked eye condition) and 25 minutes after each contact lens insertion.Results: Refractive sphere and cylinder were, respectively, -1.36 +/- 1.04 D (ranging from -6.00 to -0.25 D) and -0.23 +/- 0.30 D (ranging from -0.75 to 0.00 D). TFSQ and TFSQ area were lower (meaning more stable tear film) at baseline when compared with both contact lens types (p < 0.025). Higher pre-lens tear instability (larger TFSQ and_TFSQ area values) was found with the dual-focus than the monofocal lens. Auto Tear Break-Up Time was higher at baseline than with each of the contact lenses, without statistically significant differences between both contact lens types. Visual analogue scales revealed statistically significant better scores in the monofocal contact lens than in dual-focus contact lens for general (0.77 +/- 1.14 vs 3.12 +/- 2.79), physical (0.96 +/- 1.46 vs 2.19 +/- 2.45) and visual comfort (1.27 +/- 1.66 vs 3.92 +/- 2.04).Conclusion: A slight reduction in short-term pre-lens tear film stability was found in the dual-focus design in comparison with the monofocal lens, potentially contributing to the deterioration of visual performance and comfort during dual-focus contact lens wear.